Chemiexcitation‐Triggered Prodrug Activation for Targeted Carbon Monoxide Delivery. (21st April 2022) - Min, Qingqiang; Ni, Zihui; You, Meng; Liu, Miao; Zhou, Zhou; Ke, Hengte; Ji, Xingyue
Abstract: Photolysis‐based prodrug strategy can address some critical drug delivery issues, which otherwise are very challenging to tackle with traditional prodrug strategy. However, the need for external light irradiation significantly hampers its in vivo application due to the poor light accessibility of deep tissue. Herein, we propose a new strategy of chemiexcitation‐triggered prodrug activation, wherein a photoresponsive prodrug is excited for drug payload release by chemiexcitation instead of photoirradiation. As such, the bond‐cleavage power of photolysis can be employed to address some critical drug delivery issues while obviating the need for external light irradiation. We have established the proof of concept by the successful development of a chemiexcitation responsive carbon monoxide delivery platform, which exhibited specific CO release at the tumor site and pronounced tumor suppression effects. We anticipate that such a concept of chemiexcitation‐triggered prodrug activation can be leveraged for the targeted delivery of other small molecule‐based drug payloads. Abstract : A new prodrug strategy, namely chemiexcitation triggered prodrug activation, is proposed herein to achieve targeted CO delivery to the tumor site. The CO release from a photoresponsive CO prodrug is activated by chemical energy transfer instead of by UV irradiation. As such, the inherent limitations with light irradiation are perfectly addressed.